Características produtivas e composição bromatológica do capim marandu adubado com nitrogênio - Sales, Kyron Cabral (2017)
The objective was to evaluate the productive characteristics and bromatological composition of Brachiaria brizantha cv. Marandu submitted to fertilization with nitrogen doses. The experiment was carried out at the experimental farm Federal University of Mato Grosso, Cuiabá campus, from November 2015 to May 2017. The treatments were arranged in a completely randomized design with 7 treatments and 5 replicates, being: 0; 25; 50; 75 and 100 kg N ha-1 cut-1 in the form of ammonium sulfate. The maximum productivity, in the second year, was evidenced in the nitrogen dose of 77 kg ha-1. In the two years of evaluation, the highest yields observed were, on average, 14,500 kg DM ha-1. A quadratic effect was observed for population density of tillers, so that the highest density occurred at the dose of 83.6 kg N ha-1 cut-1. For the crude protein, a positive linear effect was observed with 14.36% in the dry matter at the highest applied dose, however, for neutral detergent insoluble fiber, it was observed a linear negative effect with reduction of 3.5% from the highest to the lowest dose. There was no effect of fertilization on the potentially digestible dry matter and the indigestible neutral detergent insoluble fiber. Thus, nitrogen fertilization increased the crude protein content by 118% in the highest dose, the maximum yield of DM, DPP and leaf blade percentage of Marandu grass was between 77 and 83 kg N ha-1 cut-1.